Depolarization and electrical stimulation enhance in vitro and in vivo sensory axon growth after spinal cord injury - Huber, Ioana; Sandner, Beatrice; Weidner, Norbert; Blesch, Armin (Experimental neurology, 2018)
Activity dependent plasticity is a key mechanism for the central nervous system (CNS) to adapt to its environment. Whether neuronal activity also influences axonal regeneration in the injured CNS, and whether electrical stimulation (ES) can activate regenerative programs in the injured CNS remains incompletely understood. Using KCl-induced depolarization, in vivo ES followed by ex-vivo neurite growth assays and ES after spinal cord lesions and cell grafting, we aimed to identify parameters important for ES-enhanced neurite growth and axonal regeneration. Using cultures of sensory neurons, neurite growth was analyzed after KCl-induced depolarization for 1-72h. Increased neurite growth was detected after short-term stimulation and after longer stimulation if a sufficient delay between stimulation and growth measurements was provided. After in vivo ES (20Hz, 2× motor threshold, 0.2ms, 1h) of the intact sciatic nerve in adult Fischer344 rats, sensory neurons showed a 2-fold increase in in vitro neurite length one week later compared to sham animals, an effect not observed one day after ES. Longer ES (7h) and repeated ES (7days, 1h each) also increased growth by 56-67% one week later, but provided no additional benefit. In vivo growth of dorsal column sensory axons into a graft of bone marrow stromal cells 4weeks after a cervical spinal cord lesion was also enhanced with a single post-injury 1h ES of the intact sciatic nerve and was also observed after repeated ES without inducing pain-like behavior. While ES did not result in sensory functional recovery, our data indicate that ES has time-dependent influences on the regenerative capacity of sensory neurons and might further enhance axonal regeneration in combinatorial approaches after SCI.
Available online 26 November 2017
Gesehen am 19.09.2018